2014
DOI: 10.1017/sjp.2014.22
|View full text |Cite
|
Sign up to set email alerts
|

INECO Frontal Screening: an Instrument to assess Executive Dysfunction in Schizophrenia

Abstract: Although several brief sensitive screening tools are available to detect executive dysfunction, few have been developed to quickly assess executive functioning. The INECO Frontal Screening (IFS) is a brief tool which has proved be useful for the assessment of the executive functions in patients with dementia. The aim of this study was to explore whether the IFS is as sensitive and specific as the BADS, a battery designed to assess the dysexecutive syndrome, in schizophrenia. Our sample comprised a group of 34 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 50 publications
(62 reference statements)
0
4
0
1
Order By: Relevance
“…The IFS was designed to include several subtests in order to measure, in an efficient way, as many EF as possible. Previous studies have shown promising diagnostic performance [6] , [7] , [8] , [9] , [10] . Thus, it arises as an encouraging alternative for early detection of dementia cases.…”
Section: Introductionmentioning
confidence: 98%
“…The IFS was designed to include several subtests in order to measure, in an efficient way, as many EF as possible. Previous studies have shown promising diagnostic performance [6] , [7] , [8] , [9] , [10] . Thus, it arises as an encouraging alternative for early detection of dementia cases.…”
Section: Introductionmentioning
confidence: 98%
“…Evidence further suggests that the IFS outperforms similar screening tool of executive dysfunction, namely the Frontal Assessment Battery, in differentiating normal controls from subjects with neurocognitive disorders (Custodio et al, 2016;Gleichgerrcht et al, 2011). In addition to age-related neurocognitive disorders, deficits on the IFS have been observed in various psychiatric conditions associated with executive dysfunction, including major depression, attention deficit and hyperactivity disorder, schizophrenia and bipolar disorder (Baez et al, 2014;Reyes et al, 2009;Silva, Monteiro, & Lopes, 2014). Taken together, these results support the validity of the IFS in detecting executive function deficits in a wide range of clinical populations.…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive state was assessed with the Montreal Cognitive Assessment (MoCA) 61 (Supplementary Material 2.1 ), a brief screening tool sensitive to cognitive dysfunction in adult ASD 62 , 63 . Executive functions were evaluated with the INECO Frontal Screening (IFS) 64 (Supplementary Material 2.2 ), a validated battery for the detection of executive-frontal dysfunction in adults with neuropsychiatric conditions 65 67 .…”
Section: Methodsmentioning
confidence: 99%